PENGARUH BIAYA OPERASIONAL PER PENDAPATAN OPERASIONAL (BOPO), NON PERFORMING LOAN (NPL) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSET (ROA)(Studi Kasus Pada PT Bank Pembangunan Daerah Nusa Tenggara Timur) - Nokas, Adriana Enggelina; Taolin, Maximus L; Manek, Aquidowaris (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2021)
This study aims to determine the effect of Operational Costs per Operating Income (BOPO), Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) on Return On Assets (ROA) (Case Study at PT Bank Pembangunan Daerah Nusa Tenggara Timur)”. Data collection techniques used are documentation and observation. The population in this study was PT Bank Pembangunan Daerah Nusa Tenggara Timur, and the sample studied was 49 respondents (49 quarters of the research variables) with the sampling technique used was purposive sampling. The data analysis techniques used are: descriptive and inferential with simple linear regression analysis tools and multiple linear regression. The results of the study show that partially the BOPO (X1) and NPL (X2) variables have a negative and significant effect on ROA of Bank NTT; while LDR (X3) has no significant effect on Bank NTT's ROA. Simultaneously, the BOPO, NPL, and LDR variables affect the ROA of NTT Bank.